PEMBERIAN POC KASCING (VERMICOMPOST) DENGAN DOSIS BERBEDA TERHADAP PERTAMBAHAN POPULASI Chlorella sp - Rizka Avif Putri Hs; Agusnimar; Rosyadi (DINAMIKA PERTANIAN, 2022)
"Giving vermicompost POC with different doses to the increase in the population of Chlorella sp." The research was carried out for 23 days starting from 10 April 2018 to 3 May 2018, at the Microalgae Laboratory of the Fish Seed Center, Faculty of Agriculture, Riau Islamic University, Pekanbaru. This study aims to determine the effect of giving vermicompost POC with different doses on the increase in the population of Chlorella sp. The method used was a completely randomized design (CRD) with 5 treatments and 3 replications, namely: P1 administration of vermicompost POC at a dose of 0.5 cc/l, P2 giving vermicompost POC at a dose of 1.0 cc/l, P3 giving vermicompost POC at a dose of 1,5 cc/l, P4 was given vermicompost POC at a dose of 2.0 cc/l and P5 was given vermicompost POC at a dose of 2.5 cc/l. From the results of the study, the highest density of Chlorella sp was in treatment P2 with a total density of 14,500,000 cells/ml on day 11. With the lowest average peak in treatment P5 with a total cell count of 6,333,333 cells/ml on day 4. Water quality such as temperatures ranging from 25-30 0C, pH 6.5-7.